Bee specific rooms for native pollinators - Stanley, Johnson; Gupta, Jai Prakash; Subbanna, Avupati RNS (Indian Farming, 2018)
Non-Apis bees are regarded as very effective pollinators of certain crops. Most of them are solitary bees and not live in colonies but make their nests for egg laying. Bee hotels with wooden logs having drilled holes, sticks with soft pith kept undisturbed can attract leaf cutter bees and small carpenter bees for building their nests. By conserving these bees in the farmlands itself by providing shelter will allow them to remain in the farm resulting in effective pollination.